2022
DOI: 10.1038/s41398-022-01803-6
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor of activated T cells 4 in the prefrontal cortex is required for prophylactic actions of (R)-ketamine

Abstract: Abstract(R, S)-ketamine has prophylactic antidepressant-like effects in rodents; however, the precise molecular mechanisms underlying its action remain unknown. Using RNA-sequencing analysis, we searched novel molecular target(s) that contribute to the prophylactic effects of (R)-ketamine, a more potent enantiomer of (R, S)-ketamine. Pretreatment with (R)-ketamine (10 mg/kg, 6 days before) significantly ameliorated body weight loss, splenomegaly, and increased immobility time of forced swimming test in lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 73 publications
(101 reference statements)
0
26
0
Order By: Relevance
“…Spleen enlargement is linked to systemic inflammation 30 . For example, we reported splenomegaly in mice treated with lipopolysaccharide (LPS), and there were positive correlations between spleen weight and blood levels of pro-inflammatory cytokines (i.e., IL-6, tumor necrosis factor-α) [31][32][33] . A chronic social defeat stress (CSDS) model revealed that the spleen weight of susceptible mice with depression-like behaviors was higher than that www.nature.com/scientificreports/ www.nature.com/scientificreports/ of control mice and CSDS-resilient mice 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spleen enlargement is linked to systemic inflammation 30 . For example, we reported splenomegaly in mice treated with lipopolysaccharide (LPS), and there were positive correlations between spleen weight and blood levels of pro-inflammatory cytokines (i.e., IL-6, tumor necrosis factor-α) [31][32][33] . A chronic social defeat stress (CSDS) model revealed that the spleen weight of susceptible mice with depression-like behaviors was higher than that www.nature.com/scientificreports/ www.nature.com/scientificreports/ of control mice and CSDS-resilient mice 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A chronic social defeat stress (CSDS) model revealed that the spleen weight of susceptible mice with depression-like behaviors was higher than that www.nature.com/scientificreports/ www.nature.com/scientificreports/ of control mice and CSDS-resilient mice 34 . Collectively, it is likely that LPS-(or CSDS)-induced splenomegaly is associated with systemic inflammation [31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that ( R )-ketamine, but not its metabolites [( R )-norketamine and (2 R ,6 R )-HNK], produced a sustained prophylactic effect in CRS-induced depression-like behaviors in mice. We previously reported that ( R )-norketamine and (2 R ,6 R )-HNK did not show antidepressant and prophylactic effects in LPS-induced inflammation, LH, and CSDS models of depression [ 28 , 44 , 62 ]. Therefore, it is likely that ( R )-ketamine itself, but not these metabolites, could have persistent prophylactic effects in CRS-exposed mice.…”
Section: Discussionmentioning
confidence: 99%
“…The locomotion (LMT), forced swimming test (FST) and sucrose preference test (SPT) were performed as described previously [ 30 32 , 44 , 56 ]. An automated animal movement analysis system (SCANET MV-40; MELQUEST Co., Ltd, Toyama, Japan) was used to measure the locomotor activity of each mouse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation